2010
DOI: 10.1111/j.1439-0426.2010.01492.x
|View full text |Cite
|
Sign up to set email alerts
|

Initial and long-term consequences of attempts to improve fish-food resources in Lithuanian waters by introducing alien peracaridan species: a retrospective overview

Abstract: Summary In this overview, we consider the rationale and practice of invertebrate introductions into Lithuanian waters, the current distribution of introduced species, test the theoretical expectations of introduction of peracaridan species into lakes, and summarize the large‐scale consequences of these translocations. After some early attempts to transfer locally available species within the country, peracaridan species from the Ponto‐Caspian region were introduced into Lithuanian waters during the 1960s (Pont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…anómala), especially in the impounded reaches and in stagnant or slow-flowing backwaters, where the species itself can find hospitable environment and the conditions of the formation of an ample Zooplankton stock are provided. It also may become an important food source of certain fish species (Bäcescu, 1954;Rakauskas et al, 2010); however, Arbaciauskas et al (2010) could not demonstrate positive effects on fish stocks in Lithuanian waters.…”
Section: Discussionmentioning
confidence: 84%
“…anómala), especially in the impounded reaches and in stagnant or slow-flowing backwaters, where the species itself can find hospitable environment and the conditions of the formation of an ample Zooplankton stock are provided. It also may become an important food source of certain fish species (Bäcescu, 1954;Rakauskas et al, 2010); however, Arbaciauskas et al (2010) could not demonstrate positive effects on fish stocks in Lithuanian waters.…”
Section: Discussionmentioning
confidence: 84%
“…Borcherding et al (2007) suspect Hemimysis are a higher quality food item (compared to zooplankton), and the reduction in zooplankton as a result of Hemimysis predation provokes a heavier fish reliance on Hemimysis to augment their diet. In contrast, Arbačiauskas et al (2010) concluded no growth or production advantage was evident for European perch when comparing lakes with and without introduced mysids in Lithuanian waters. While both the Borcherding et al (2007) and Arbačiauskas et al (2010) studies reached different conclusions regarding the effect of Hemimysis on fish growth and production, both groups agree that Hemimysis will reduce resident zooplankton density in invaded waters.…”
Section: Introductionmentioning
confidence: 81%
“…However, previous stable isotope studies in the LGL suggest opportunistic omnivory regardless of size (Marty et al, 2010). Hemimysis, in turn, are consumed by a variety of fish species, including alewife, round goby, yellow perch and rock bass (Borcherding et al, 2007;Arbačiauskas et al, 2010;Lantry et al, 2010;Fitzsimons et al, (2012-this issue)). …”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…It has been suggested that this invasive amphipod will provide a plentiful food resource for fish that traverse the predatory gauntlet (Luecke et al 1990) to reach adulthood, perhaps boosting survival and fecundity (Kelleher et al 1998;Madgwick and Aldridge 2011;Brandner et al 2013;Czarnecka et al 2014). However, the higher density of D. villosus could just compensate for its lower quality and profitability as prey (Arbaciauskas et al 2010;Błońska et al 2015) and so provide little additional benefit to fish populations.…”
Section: Villosusmentioning
confidence: 99%